Faktor yang Memengaruhi Penundaan Kehamilan Pada Pernikahan Remaja Usia 14-19 Tahun Di 2 Kabupaten Provinsi Gorontalo - Eka Fitriani Sujitno; Hermanto Tri Joewono; Margarita M Maramis (Jurnal Keperawatan Muhammadiyah, 2019)
The incidence of marriage at a young age is till very  high in Indonesia. Indinesia is the 37th country with  a high prevalence of young marriage in the world and the second highest in ASEAN after Cambodia (UNDESA, 2010). According to BPS (2015), Gorontalo Province is ranked 5th based on the prevalence of marriage of girls aged 15-19 years. The purpose of this study was to analyze the factors that influence the delay of pregnancy in teenage marriages aged 14-19 years. The methodology used is the case control design. Research subjects were married women aged 14-19 years in 2015-2017 in 2 districts Gorontalo province who realize the inclusion criteria. Number of samples for each group of 75 respondents for cases and controls. Statistical analysis was performed by chi square technique and logistic regression analysis method. Results: shows the factors that influence the delay of pregnancy in adolescent marriage are wife's age (p = 0,000, OR = 8,889, 95% CI = 2,887-27,375) and family support (p = 0,000, OR = 28, 95% CI = 7,793- 100,612). The conclusion of this study is that the wife's age and family support have a significant relationship to the delay of pregnancy in adolescent marriage. Disorder towards toddlers by 2,5 times.